FINANCIAL LITERACY, SELF EFFICACY, DAN FINANCIAL ATTITUDE TERHADAP FINANCIAL MANAGEMENT BEHAVIOUR UMKM DENGAN GENDER VARIABEL MODERASI - Hikmah Hikmah; Risca Azmiana (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Attaining effective financial management behavior necessitates possessing the awareness, knowledge, competencies, attitudes, and actions essential for making prudent financial choices. In the context of gender's moderating influence, this research aimed to determine the influence of financial literacy, self-efficacy, and attitudes on the financial management behavior of micro, small, and medium-sized enterprise (MSME) participants. The study employed associative research methodologies and utilized a survey questionnaire for data collection. The research sample comprised 204 participants, determined using the Jacob Cohen formula. The primary instrument employed in the study was a questionnaire. The data were analyzed using the Partial Least Squares (PLS) technique within the Structural Equation Modeling (SEM) framework. The results revealed that Financial Literacy positively and significantly impacts the financial management behavior of MSME participants, alongside Self-Efficacy and Financial attitude, both of which also exerted positive and significant influences on the financial management behavior of these individuals. Additionally, gender exhibited a notable and meaningful impact, serving as a moderator in the relationship between Financial Literacy and the financial management behavior of MSME participants.